The contribution of ethnography to understanding nursing work - Murphy, Fiona (Obzornik zdravstvene nege, 2014)
Introduction: This methods paper examines ways in which ethnography and in particular the ethnographic method of participant observation, informs understanding of the reality of nursing work. Methods: The relevance of ethnography for nursing practice is illustrated through three ethnographic studies of nursing work, all of which involved participant observation for periods of over twelve months. These studies were conducted in three different hospital settings in Wales, United Kingdom; an intensive therapy unit, a gynaecological unit and a medical admissions unit. Definitions of ethnography are considered along with an account of three key ethnographic methods; participant observation, interviews and documentary analysis. Results: Two key themes which were apparent in all three of these ethnographies will be presented to demonstrate the contribution of ethnography in understanding nursing practice. These themes are; the embodied nature of nursing work and duality and tension in nursing work. Discussion and conclusion: It will be argued that ethnography as a research approach enables nursing practice to be understood as it is actually experienced in the uncertain, disruptive and often resource limited context of contemporary healthcare.
Keywords: ginekologija; gynaecology; intensive care; intenzivna nega; medical admissions; nujni sprejem bolnika; nursing care; opazovanje z udeležbo; participant observation; raziskovalne metode; research methods; zdravstvena nega